The Existence of Justice Collaborators in Corruption Crimes: Challenges and Legal Policies - Ismaidar Ismaidar; Abdul Rahman Maulana Siregar; Sagita Purnomo; Rohasiholan Doloksaribu; Bima Lumbanbatu (Journal of Innovative and Creativity (Joecy), 2026)
This research aims to discuss in depth the role and effectiveness of justice collaborators in law enforcement of corruption crimes, as well as comprehensively discuss the obstacles and legal policies for the implementation of justice collaborators in corruption crimes. The type of research used is normative juridical with a descriptive-analytical approach, discussing existing legal symptoms and problems and testing them based on applicable laws and regulations and legal norms. The results of this study show that the role of justice collaborators is to reveal and provide information and supporting evidence to law enforcement officials, as well as to give testimony at the trial about the mode, how, and where and who received the money from corruption. The existence of justice collaborators in law enforcement for corruption crimes has not been fully effective because there are still inconsistencies in information or confessions by justice collaborators in trials. Obstacles to the implementation of justice collaborators in corruption crimes include: the absence of legal arrangements, suboptimal protection, the disparity of the judiciary, and the status as the main perpetrators of the crime.